(untitled) - Frazier, Charles (New York, 1998)
The impact of the Civil War on lovers. Inman is not the man he used to be, as wounded in battle he slowly makes his way home to North Carolina. His sweetheart, Ada, too has changed, no longer a flighty belle but a hard-working farm woman. Will love be the same?
Keywords: Chuyện tình,Love stories,United States,Hoa Kỳ; History,Fiction,Lịch sử,Tiểu thuyết; Civil War, 1861-1865,Nội chiến, 1861-1865